A new species of spider wasps (Hymenoptera: Pompilidae) from Panama: Mystacagenia kimseyae sp. nov. - Cambra, Roberto A.; Wasbauer, Marius S.; Corro-Chang, Patricia (Zootaxa, 2020)
Mystacagenia Evans, 1973 is a strictly Neotropical genus of pompilid wasps (Pepsinae: Ageniellini), restricted to rain forest areas. The genus comprises four described species: M. albiceps Evans, 1973 (Peru, Brazil), M. bellula Evans, 1973 (Peru), M. variegata Evans, 1973 (Brazil), and M. elegantula Evans, 1980 (Panama). Mystacagenia is scarce in collections, with only eight specimens registered, all of these females (Evans 1973, 1977, 1980; Cambra 1993; Corro & Cambra 2011).